(3GdYWGA GdLRjd aj cTa GdJQSjds - (3eMeO Hf CMeO Hf YGeQ GdHdhj GdSGdej GdWQWhTj, CHh YGeQ,J (B559 (3g` s
(3ChdgG (B:s
(3QLGdg GdMSf Hf hUa CHh GdaJM Hf CHj GdaVd Hf s
(3BNQgG (B:s
(3QSGdI ef EfTGA GdcGJH GdCOjH GdeGLO GdMSjH CHj eMeO Hf MGeO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(6148) s
Keywords: (3GdCOHs